Development and psychometric properties of the Academic Mindfulness Scale for university students - Al-Qurashi, Khadijah Dhaifallah; Matar, Abdel Fattah Ragab (International Journal of Innovative Research and Scientific Studies, 2025)
Academic environments require specialized measurement instruments for mindfulness assessment. This study developed and validated the Academic Mindfulness Scale (AMS) to address the gap in context-specific mindfulness measures for university students in Saudi Arabia. Using a quantitative approach with 553 undergraduates (311 males, 242 females, aged 18-26), we developed the AMS through literature review, expert consultation, and pilot testing. Factor analyses revealed a four-factor structure explaining 57.098% of variance: Academic attention in the classroom (33.072%), Academic acceptance without judgment (9.994%), Performing academic tasks with full awareness (7.639%), and Academic presence in the present moment (6.394%). Confirmatory factor analysis supported this structure (χ² = 689.248, CFI = .871, RMSEA = .076). The 20-item scale demonstrated excellent reliability (α = .889, ω = .911) with satisfactory subscale reliability (α = .775–.818) and item-total correlations ranging from .42 to .64 (p < .01). The AMS provides a valid, reliable tool for assessing academic mindfulness among university students, offering educators and researchers a targeted instrument to evaluate mindfulness interventions, identify students needing support, and enhance academic engagement. This scale moves beyond adaptations of general mindfulness measures to provide a nuanced understanding of mindfulness specifically in educational contexts.